Inflammaging in Endemic Areas for Infectious Diseases - Batista, Marina Andrade; Calvo-Fortes, Fernanda; Silveira-Nunes, Gabriela; Camatta, Giovanna Caliman; Speziali, Elaine; Turroni, Silvia; Teixeira-Carvalho, Andrea; Martins-Filho, Olindo A.; Neretti, Nicola; Maioli, Tatiani Uceli; Santos, Rodrigo Ribeiro; Brigidi, Patrizia; et al. (Frontiers in Immunology, 2020)
Immunosenescence is marked by a systemic process named inflammaging along with a series of defects in the immunological activity that result in poor responses to infectious agents and to vaccination. Inflammaging, a state of low-grade chronic inflammation, usually leads to chronic inflammatory diseases and frailty in the elderly. However, some elderly escape from frailty and reach advanced age free of the consequences of inflammaging. This process has been called immunological remodeling and it is the hallmark of healthy aging as described in the studies of centenarians in Italy. The biological markers of healthy aging are still a matter of debate and the studies on the topic have focused on inflammatory versus remodeling processes and molecules. The sub-clinical inflammatory status associated to aging might be a deleterious event for populations living in countries where chronic infectious diseases are not prevalent. Nevertheless, in other parts of the world where they are, two possibilities may occur. Inflammatory responses may have a protective effect against these infectious agents. At the same time, the long-term consequences of protective immune responses during chronic infections may result in accelerated immunosenescence in these individuals. Therefore, the biological markers of healthy aging can vary according to environmental, cultural and geographical settings that reflect worldwide, and in a non-biased, non-westernized perspective, the changes that we experience regarding our contacts with microorganisms and the outcomes of such contacts.